INVETARISASI DAERAH PENTING BAGI IKAN DI SUMATERA SELATAN - Muhammad Iqbal (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2004)
The exceptional fish biodviserty resource of South Sumatera Province must be utilized optimally in order to increase the well-being of the South Sumatera people in short and long terms. This means that utiliziation should be based not only on economical consideration but also on ecological and environmental principles, and should be under-pinned by the principle of sustainable use. Identification of important fish area in South Sumatera as a tool for help conserving fish biodiversity. In this paper, a place may be identified as important fish area or “fish hot-spot” it fulfill one of four criterias: important wetland area, protected area, level of endemism or important fish species in the area and occurrence of other species as indicator. Based on these criterias, 20 sites have been identified as important fish area in South Sumatera. Keywords: important area, fish, South Sumatra